Isolation of cells from rabbit renal proximal tubules by using a hyperosmolar intracellular-like solution. - Nagineni, C N (1984)
A novel method of isolation of cells from rabbit kidney proximal tubules by using an intracellular-like solution (ICS) and gentle mechanical agitation in the absence of enzymes or chelators is described. Metabolic and functional characteristics of these cells were studied after washing and resuspension in modified Hanks medium, and the results were compared with those obtained in cells similarly prepared in extra-cellular-like solution (ECS). Trypan Blue exclusion and protein content were not different between the two preparations. However, oxygen consumption, ATP content and time- and concentration-dependent rates of uptake of phosphate, alpha-methyl glucoside and L-alanine were severalfold higher in cells prepared in ICS. Na+-dependent uptake of these solutes was 95% and 80% of total uptake in cells prepared in ICS and ECS respectively. Maximum transport rates (Tmax.) of phosphate, alpha-methyl glucoside and L-alanine were significantly higher in cells prepared in ICS. We propose that the use of ICS in the isolation procedure would yield a functionally more viable cell preparation, and therefore provides an ideal model for transport and metabolic studies at a cellular level.